Mental Health Care Use and Associated Factors in Systemic Sclerosis: A Scleroderma Patient‐Centered Intervention Network Cohort Study. Issue 8 (23rd May 2022) - Becetti, Karima; Nguyen, Joseph T.; Kwakkenbos, Linda; Carrier, Marie‐Eve; Tao, Lydia; Gordon, Jessica K.; Mancuso, Carol A.; Welling, Joep; Mouthon, Luc; Bartlett, Susan J.; Malcarne, Vanessa L.; Thombs, Brett D.; et al.
Abstract : Objective: Systemic sclerosis (SSc) has significant psychosocial implications. We aimed to evaluate the proportion of participants in a large international SSc cohort who used mental health services in a 3‐month period and to evaluate demographic, psychological, and disease‐specific factors associated with use. Methods: Baseline data of participants enrolled in the Scleroderma Patient‐Centered Intervention Network Cohort were analyzed. We determined the proportion that used mental health services and the source of services in the 3 months prior to enrollment. Multivariable logistic regression was used to identify variables associated with service use. Results: Of the 2319 participants included in the analysis, 417 (18%) used mental health services in the 3 months prior to enrollment. General practitioners were the most common mental health service providers (59%), followed by psychologists (25%) and psychiatrists (19%). In multivariable analysis, mental health service use was independently associated with higher education (odds ratio [OR] 1.07, 95% confidence interval [CI] 1.03‐1.11), smoking (OR 1.06, 95% CI 1.02‐1.11), being retired (OR 0.60, 95% CI 0.38‐0.93), having limited SSc (OR 1.39, 95% CI 1.02‐1.89), and having higher anxiety symptom scores (OR 1.04, 95% CI 1.03‐1.06) and lower self‐efficacy scores (OR 0.90, 95% CI 0.83‐0.97). Variables not significantly associated included age, race, disease manifestations, depression symptom scores, and body image distress. Conclusion: About 18% of participants in a large international cohort received mental health services in a 3‐month period, of whom the majority received these services from a general practitioner.